(untitled) (Communication & Society, 2015)
Using quantitative analysis, complaints received by the Observatorio de la Imagen de las Mujeres (Monitoring Centre for the Portrayal of Women) during the period of 1999-2009 have been studied. This is with the objective of understanding the evolution of content that has been classified as unlawful advertising in the framework of article 3 of the General Advertising Law, 10 reports have been examined. The results show that in the Spanish advertising domain, the use of the female stereotype as an object is no longer a recurring element; however, sexism maintains its presence through other criteria that also trigger complaints.